Interview with Joseph Petric - Goldman, Jonathan (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2004)
In this interview, Joseph Petric, the internationally acclaimed concert accordionist, shares his thoughts on his personal artistic development, on his relationship to the works of the past, and on his 'plurivocal' (Eco) view of the conflicting aesthetic tendencies which lie at the heart of today's concert music. His relationship with his somewhat unusual instrument turns out to be inseparable from his undying support for contemporary and even experimental music. His goal is to produce, sometimes ironically, an authentic artistic enunciation.